THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON CUSTOMER LOYALTY AT FORE COFFEE IN SURABAYA: PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP LOYALITAS PELANGGAN PADA FORE COFFEE DI SURABAYA - Raisha Firliana Listanti; Taufik Setyadi; Nisa Hafi Idhoh Fitriana (Universitas Hamzanwadi, 2026)
Intense competition in the coffee retail sector has compelled companies to prioritize customer relationship management to foster sustainable loyalty. This research analyzes the influence of CRM on the loyalty of Fore Coffee users in Surabaya, utilizing a quantitative explanatory approach. Drawing from a sample of 100 respondents selected through purposive sampling, the data were analyzed using the SEM-PLS method. The findings confirm a positive and significant impact of CRM on customer loyalty, with a contribution of 74.9% (R^2 0.749). This indicates that digital CRM strategies, including loyalty programs and personalized promotions, play a pivotal role in strengthening consumer engagement. Consequently, reinforcing CRM systems serves as a strategic move for coffee shop management to maintain their customer base amidst an increasingly aggressive industrial competition